Effect of Endosulfan and Carbofuran on Enzyme Activities in Clarias Gariepinus (African Catfish) - Daryani (2003)
Determination of lethal concentration (LC₅₀) of carbofuran and the effect of a sub lethal concentration of endosulfan and carbofuran on glutathione S-transferase (GST), glutathione peroxidase (GPx) and ethoxyresorufin O-deethylase (EROD) activities were investigated in the liver and intestine (proximal, medial and distal) of Clarias gariepinus (African catfish). The 96-h LCso for carbofuran in present study was 1.63 mg/I. Endosulfan and carbofuran treatment resulted in a significant increase (p<0.05) of EROD, GST and GPx in liver and intestine (proximal, medial and distal) at the sub-lethal concentrations of 10.8 µg/l and 0.82 mg/l, respectively. Endosulfan enhanced GST GPx and EROD enzymes activity in the liver and intestine (proximal, medial and distal) of treated fish. The fish were examined every four days for twenty days. The results showed that all the enzyme activities were maximum after day four exposure and decreased until the termination of the experiment. The activity of GST in all of the organs of treated fish exposed to carbofuran decreased linearly after 2 hours exposure until day 20. However GPx activity in all of the organs of treated fish exposed to carbofuran decreased after day 4 followed by an increase up to day 16 and decreased further until the termination of the experiment. The EROD activity in all of the organs exposed to carbofuran has a similar trend with that when exposed to endosulfan. Both activities, exposed to carbofuran and endosulfan increased until day 4 followed by a gradual decrease until day 20. In general, GST and GPx activity in all parts of the intestine of Clarias gariepinus (African catfish) is significantly higher than those in the liver. Compared to GST and GPx, EROD activity in the liver showed significantly higher activity than that found in the intestinal organs.